2018
DOI: 10.1111/sdi.12667
|View full text |Cite
|
Sign up to set email alerts
|

A practical guide for the care of patients with end‐stage renal disease near the end of life

Abstract: Most patients who rely on dialysis for treatment of end-stage renal disease (ESRD) never receive a kidney transplant. Therefore, it is important for nephrology providers to feel comfortable discussing the role of dialysis near the end of life (EOL). Advance care planning (ACP) is an ongoing process of learning patient values and goals in an effort to outline preferences for current and future care. This review presents a framework for how to incorporate ACP in the care of dialysis patients throughout the kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…This is likely, at least in part, due to clinicians inadequately explaining the realities of advanced CKD trajectory and prognosis throughout the disease course, which would be needed to help dispel such misperceptions. 22 Additionally, low health literacy in our particular population likely serves as a barrier to communication about end-of-life choices, as Ladin et al 23 found in their study of end-of-life discussions among dialysis patients 75 years and older.…”
Section: Discussionmentioning
confidence: 88%
“…This is likely, at least in part, due to clinicians inadequately explaining the realities of advanced CKD trajectory and prognosis throughout the disease course, which would be needed to help dispel such misperceptions. 22 Additionally, low health literacy in our particular population likely serves as a barrier to communication about end-of-life choices, as Ladin et al 23 found in their study of end-of-life discussions among dialysis patients 75 years and older.…”
Section: Discussionmentioning
confidence: 88%
“…We found that respiratory distress was the most common trigger to both EDP and IPA compared to findings in other studies of patients with CKD [ 8 ] or cancer [ 54 ] where pain was more likely to trigger an EDP. Patients with advanced CKD will benefit from palliative care input to initiate end-of-life discussions and to help determine future goals of care [ 55 ] such as their preferred place of care and withdrawal from dialysis. Furthermore, in collaboration with renal services, PCS can provide support with symptom management, and psychological support and education for both the patient and carer to manage expected exacerbation of symptoms such as breathlessness and pain [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hospice and early palliative care are generally considered as an alternative and supportive care to offer symptoms relief and optimize the quality of life among ESRD patients [ 2 , 3 , 4 , 5 , 6 , 7 ]. However, discontinuing intensive dialysis and receiving hospice care can be a more difficult decision than withholding treatment, and thus, hospice remains underutilized for ESRD patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%